Knowledge Management in India : A Case Study of an Indian Bank - Goswami, Chandana (Journal of Nepalese Business Studies, 2009)
Knowledge Management is among one of the buzzwords prevailing in the management circles. It is seen as a tool which can create a strategic impact. Theoretically knowledge management is seen to have the potential to influence many spheres of an organization. It is available in a variety of forms and to a large extent the hidden tacit knowledge can be codified and made explicit. It is believed that by sharing of knowledge, the organization will benefit in the long run. However the success of knowledge management lies in the role played by the organization, the developers and the users themselves. This paper makes an exploratory study about Knowledge Management in practice at ICICI (India) and tries to identify the critical success factors of Knowledge Management. A small survey was done among 31 employees of ICICI and based on their responses a factor analysis was carried out. This resulted in identification of the critical success factors. A personal observation of the system at work also makes attempt to understand whether Knowledge Management can fulfill some of the needs of the technical and professional workforce. Key words: Knowledge Management, India, ICICI, initiating, implementing, iacit, explicit The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 37-49